1999
DOI: 10.1007/s11064-004-1826-2
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Is an Essential Factor for Myelination

Abstract: It has been established that oligodendrocytes, the myelin forming cells, participate in iron homeostasis through the synthesis and secretion of transferrin. Here we investigated whether a correlation exists between myelination, the commonly studied function of oligodendrocytes, and that of transferrin synthesis and secretion. We used a proteolipid protein mutant, the myelin deficient rat, whose condition is characterized by severe hypomyelination. We compared the ontogenic profile for transferrin gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 30 publications
4
31
0
Order By: Relevance
“…It is difficult at this stage of the research to say whether and how the abnormalities in iron metabolism in the SC of TGX rats play a role in the pathogenesis of myelinolytic damage of the CNS of Cbl-D rats. Our present finding of unmodified Tf gene expression in SC of TGX rats further supports the notion that SCD-like lesions are purely myelinolytic, because Tf synthesis is greatly reduced in the CNS of myelin-mutant or myelindeficient mice Espinosa de los Monteros et al, 1999). One of these studies, however, using a model of impaired myelination, indicated the SC as a part of the CNS in which Tf expression is apparently insensitive to the defect of myelin synthesis .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is difficult at this stage of the research to say whether and how the abnormalities in iron metabolism in the SC of TGX rats play a role in the pathogenesis of myelinolytic damage of the CNS of Cbl-D rats. Our present finding of unmodified Tf gene expression in SC of TGX rats further supports the notion that SCD-like lesions are purely myelinolytic, because Tf synthesis is greatly reduced in the CNS of myelin-mutant or myelindeficient mice Espinosa de los Monteros et al, 1999). One of these studies, however, using a model of impaired myelination, indicated the SC as a part of the CNS in which Tf expression is apparently insensitive to the defect of myelin synthesis .…”
Section: Discussionsupporting
confidence: 88%
“…The role of deranged iron metabolism in the pathogenesis of some neurological diseases has recently attracted considerable attention, because there is evidence of iron accumulation in the brain of patients with neurodegenerative diseases such as Parkinson and Alzheimer disease (Beard et al, 1993;Gelman, 1995;Loeffler et al, 1995;Thompson et al, 2001), or demyelinating disease such as multiple sclerosis (Beard et al, 1993). From an experimental point of view, it has been demonstrated that Tf expression is critical for the function and myelinogenesis of oligodendrocytes in mice with myelinopathies Espinosa de los Monteros et al, 1999), and that ferritin overexpression, after the targeted deletion of the iron regulatory protein (IRP)-2 gene in mice, leads to neurodegeneration due to iron accumulation in brain white matter and oligodendrocytes (LaVaute et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with Lewohl et al (2000), changes were observed in the expression of myelin associated glycoprotein, apolipoprotein D, glial fibrillary acidic protein, oligodendrocytemyelin glycoprotein, and myelin proteolipid protein. In addition, another gene, transferrin, which is essential for myelination (Espinosa de los Monteros et al 1999), was changed in the present study. Previously, these genes were reported to be decreased in the frontal cortex of a case group of alcoholics, whereas in the current study the direction of change in differential expression was case group-dependent.…”
Section: Discussionmentioning
confidence: 82%
“…[10][11][12] During neurodevelopment, iron is also involved in functions such as myelination and dendritic arborization. [13][14][15][16][17][18] Thus, IDA could contribute to impaired brain development, learning, and memory. 2,13,19 Iron is also critical for regulating dopaminergic activity and iron deficiency has been implicated in neurobehavioral disorders such as ADHD.…”
Section: Introductionmentioning
confidence: 99%